155k views
0 votes
Help. What’s the correct answer?

Help. What’s the correct answer?-example-1
User AMother
by
4.8k points

2 Answers

3 votes

Answer:


f(g(24)) = -36

Explanation:

We are given the following functions and we are to find
f(g(24)):


f ( x ) = - 9 x + 9


g ( x ) = √(x+1)

Now finding
f ( g ( 2 4 ) ):


f ( g ( 2 4 ) )
= - 9 \sqrt { x + 1 } + 9


= - 9 \sqrt { 2 4 + 1 } + 9


= - 9 \sqrt { 2 5 } + 9


= - 9 * 5 + 9


= - 4 5 +9


= - 3 6

User Ropez
by
5.3k points
4 votes

Answer:

f(g(x)) = -9(sqrt(x + 1) ) + 9

-36

Explanation:

This is easier to see if you use the expanded notation.

f(g(x)) = ?

But what that means is that the left most function is f(x) and where every you see an x, you put in a g(x) like so

f(g(x)) = -9(g(x)) + 9 Now substitute the right side of g(x) into the equation for f(x)

f(g(x)) = -9(sqrt(x + 1) ) + 9

Edit to get the numerical answer.

This should be your answer or the expression that will give you the answer.

f(g(24)) = -9(sqrt(24+1) ) + 9

f(g(24)) = -9sqrt(25) +9

f(g(24)) = - 9*5 + 9

f(g(24)) = - 45 + 9

f(g(24)) = - 36

User BarthesSimpson
by
5.5k points